Unit operations in chemical enigineering - McCabe, Warren L. (Warren Lee), 1899- 190614; Smith, Julian C. (Julian Cleveland), 1919- 190629; Harriott, Peter 448981 (New York, NY : McGraw-Hill, 2005)
Noorhalieza Ali;